Program Calculation and Design Heat Pump Dryer Combined Gravitational Heat Pipe - Nguyen , Thành Luân; Nguyen , Thế Bảo (Journal of Technical Education Science, 2018)
The article describes the program for calculating and designing heat pump dryers combined with gravitational heat pipes. This program, which has been witten in EES ((Engineering Equation Solve) Platform. An experimental model of a heat pump dryer combined with gravitational heat pipes was designed and manufactured to validate the written program. The comparisons between the calculated results from the program and experimental results showed that the written program gave acceptably accurate computational results and could be used to calculate and design heat pump dryers combined with gravitational heat pipes. The use of heat pump technology to dry Centella Asiatica tea can help to save energy consumption and improve the quality of the product compared with those from traditional drying technology.